Ingredients from integral valorization of Isabel grape to formulate goat yogurt with stimulatory effects on probiotics and beneficial impacts on human colonic microbiota in vitro - Francyeli Araújo Silva; Rita de Cássia Ramos do Egypto Queiroga; Evandro Leite de Souza; Glenise Bierhalz Voss; Maria Manuela Estevez Pintado; Margarida Angélica da Silva Vasconcelos (Food Science and Human Wellness)
Isabel grape (IG) products have high contents of phenolic compounds and fiber recognized for their positive impacts on microorganisms associated with health benefits to host. This study evaluated the effects of goat yogurts formulated with ingredients from IG integral valorization on the growth and metabolism of different probiotic strains, as well as on the population of selected bacterial groups and metabolic activity of human colonic microbiota in vitro. Goat yogurts with IG ingredients (IGI) stimulated the growth of tested Lactobacillus and Bifidobacterium probiotic strains during a 48-h cultivation, as well as decreased the pH values and enhanced the organic acid production. Goat yogurts with IGI increased the population of Lactobacillus spp. and Bifidobacterium spp. during a 24-h in vitro colonic fermentation. A stable Firmicutes:Bacteroidetes ratio close to 1 was found in media with goat yogurt formulations during the colonic fermentation, being similar to the effect caused by fructooligosaccharides. Goat yogurt formulations with IGI caused increased production of short-chain fatty acids and sugar consumption during colonic fermentation. Goat yogurts with IGI should be a valuable strategy for development of novel added-value foods with beneficial effects on gut microbiota and human health.